A NEW SPECIES of COSMOCERCOIDES (NEMATODA: COSMOCERCIDAE) FROM A GYMNOPHTHALMID LIZARD of WESTERN BRAZIL - Avila, Robson W. [UNESP]; Strussmann, Christine [UNESP]; da Silva, Reinaldo J. [UNESP] (Amer Soc Parasitologists, 2010)
Cosmocercoides sauna n. sp., an intestinal parasite of the gymnophthalmid lizard Iphisa elegans from western Brazil, is described. of the 18 species previously described, C. sauna represents the 19th species, and is the third to be reported in the Neotropical region. Moreover, C sauna is the second species reported from a reptilian host and is distinguished by a smaller number of rosette papillae (4 pairs). Additionally, the new species can be distinguished from the other Neotropical species (Cosmocercoides lilloi Ramallo, Bursey and Goldberg, 2007 and C. variabilis (Harwood, 1930)) by possessing smaller spicule size and presence of both gubernaculum and lateral alae in Cosmocercoides lilloi.